Dutch care environments for people with dementia: impressions from the perspectives of an architect and a gerontologist. Issue 2 (2nd April 2020) - Shannon, Kay; Jurgenhake, Birgit
Abstract : Purpose: The purpose of this paper is to discuss Dutch innovative care environments for older people, including those living with dementia, from the perspectives or an architect and a social gerontologist. Design/methodology/approach: The authors visited three care environments for older people, each offering an innovative approach to living housing older people, including people with dementia. The settings are discussed from two disciplinary perspectives, facilitating an understanding of the influence of the built environment on daily life for residents. Findings: The three facilities were all architecturally varied and resembled "real" homes to varying degrees. Additionally, each entrance offered a different welcome to the external community, ranging from full accessibility to a closed and fortified appearance. Within each facility, the built environment afforded residents opportunities to participate in valued activities, including interacting with members of the wider community. Originality/value: The inclusion of two disciplinary perspectives offers a richer discussion of the physical and social aspects of the care environments that would be offered by one perspective alone.